THE ROLE OF ARTIFICIAL INTELLIGENCE IN FOREIGN LANGUAGE LEARNING - Zafarova Nilufar Zafar qizi, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract. This article analyzes the pivotal role of artificial intelligence (AI) technologies in foreign language learning. Research findings demonstrate that AI-based systems significantly enhance learner outcomes by creating personalized learning environments with real-time correction capabilities. The study examines various AI approaches, including machine learning, natural language processing, and chatbot technologies. The primary objective of this research is to elucidate how AI technologies offer new opportunities while simultaneously presenting challenges in the rapidly evolving field of education. The study integrates recent empirical evidence with theoretical frameworks to provide comprehensive insights into AI's transformative potential in language pedagogy.